Naval engagements : patriotism, cultural politics, and the Royal Navy, 1793-1815 - Jenks, Timothy (OUP E-Books., 2006)
Naval Engagements explores the role of the Royal Navy in eighteenth-century political culture. This was the legendary age of sail, in which heroic commanders such as Admiral Nelson won great victories for Britain. Timothy Jenks reveals the ways in which these battles and the heroes who fought them were deployed in British politics. - ;The construction of an important element in British national identity is explored in Naval Engagements, looking at the ways in which the navy - a major symbol of national community - was given meaning by a range of social groupings. The study is at once a cultura.